2001
DOI: 10.1007/s004420000500
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic N2 fixation of Alnus incana ssp. rugosa in shrub wetlands of the Adirondack Mountains, New York, USA

Abstract: Surface waters in forested watersheds in the Adirondack Mountains and northern New York State are susceptible to nitrogen (N) saturation. Atmospheric deposition of N to watersheds in this region has been measured but the extent of internal N inputs from symbiotic N fixation in alder-dominated wetlands is not known. We estimated N fixation by speckled alder in these wetlands by the N natural abundance method and by acetylene reduction using a flow-through system. Foliar N derived from fixation (%N) was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…In more concrete terms, according to Myrold and HussDanell (2003) the percentage of N derived from the atmosphere ranges between 70% and almost 100%. Similarly Hurd et al (2001) reported that speckled alder (Alnus incana ssp. rugosa) was able to derive 85-100% of its foliar N from N 2 fixation.…”
Section: Resultsmentioning
confidence: 99%
“…In more concrete terms, according to Myrold and HussDanell (2003) the percentage of N derived from the atmosphere ranges between 70% and almost 100%. Similarly Hurd et al (2001) reported that speckled alder (Alnus incana ssp. rugosa) was able to derive 85-100% of its foliar N from N 2 fixation.…”
Section: Resultsmentioning
confidence: 99%
“…Vegetation may also influence nitrification and denitrification by influencing the oxygen concentration of the wetland substrate within the rhizosphere (Armstrong, 1964) or by providing bacteria which can fix N in root nodules, such as in the wetland tree Alnus spp. (Hurd et al, 2001). There is evidence that N removal efficiency is not affected by the length of time the wetland has received N pollution while, in contrast, the ability of a wetland to remove P is known to decline with time (Nichols, 1983;Richardson, 1985).…”
Section: How Can Wetlands Change Nutrient Loads?mentioning
confidence: 99%
“…Due to the importance of various Alnus species with respect to forest ecosystem N cycling, the abundance of speckled alder within each plot was assessed by assigning a value representing no alder present (0), some alder present (1), or abundant alder present (2). Alder species support symbiotic Nfixing bacteria in root nodules and can provide a significant internal source of N to alder-dominated terrestrial ecosys-tems (Wurtz 1995;Hurd et al 2001). Depths of forest floor horizons were determined at seven locations within each plot and moss plus L, F, and H layers were sampled separately from 0.1 m 2 quadrats.…”
Section: Site Selection Instrumentation and Samplingmentioning
confidence: 99%